Elastic buckling analysis of steel-strip-stiffened trapezoidal corrugated steel plate shear walls. (September 2021) - Feng, Lifei; Sun, Tianshu; Ou, Jinping
Abstract: The overall instability of trapezoidal corrugated steel plate shear walls (TCSPSWs), induced by out-of-plane buckling, has been a major influencing factor on its seismic performance. Steel strips are believed to be effective in restricting out-of-plane buckling and improving the seismic performance of TCSPSWs. This paper investigates the elastic buckling behavior of vertical TCSPSWs stiffened by horizontal steel strips. Theoretical model based on the orthotropic plate theory is established in this study by applying the elastically torsional-restrained edges to the TCSPSW model. Based on minimum potential energy theory and Rayleigh-Ritz method, the elastic buckling load of the stiffened TCSPSWs can be solved. Besides, the critical rigidity ratio for stiffened TCSPSWs is proposed and illustrated with several calculation examples. According to the above analyses, the relationship between the rigidity ratio and elastic buckling coefficient for the stiffened TCSPSWs can be further established, and procedures to calculate the elastic coefficient for stiffened TCSPSWs at the global buckling stage are proposed. Finally, finite element (FE) model is developed to validate the theoretical model, based on which parametric studies are conducted to explore the influences of several design parameters on elastic buckling, including ratio of rigidity constants, width-to-height ratio, and thickness of the trapezoidal corrugated steel plate, etc. Results show that the proposed theoretical solution can be applied to describe the elastic buckling behavior of stiffened TCSPSWs with enough accuracy in practical design. Graphical abstract: Unlabelled Image Highlights: Steel-strip-stiffened TCSPSWs can be applied to modular building structures. Elastic buckling loads of steel-strip-stiffened TCSPSWs are calculated by running a program in MATLAB. Formula of critical rigidity ratios is proposed. Formulas of elastic buckling coefficients of steel-strip-stiffened TCSPSWs are proposed. Effects of deign parameters on buckling behavior of stiffened TCSPSWs are investigated theoretically and numerically.